KONFLIK PENGELOLAAN SAMPAH DI DKI JAKARTA DAN UPAYA MENGATASINYA - Raden Mohamad Mulyadin; Kuncoro Ariawan; Mohamad Iqbal (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2018)
Conflict of waste management is interesting to be investigated. Bantargebang as a government project on waste management in Jakarta and Bekasi areas is a community based waste management which has both positive and negative impacts. This research aims to collect information on the history of waste management conflict in DKI Jakarta, identify stakeholders, analyze the cause of waste management conflict and provide alternative solutions to solve the problem. This research used case study method with qualitative analysis approach. The result showed that waste management conflict in DKI Jakarta area involves various parties i.e: DKI Jakarta Provincial Government, Jakarta City Council D Commission, PT Godang Tua Jaya, and Commission A of DPRD Kota Bekasi. Factors causing conflict in the management of Bantargebang TPA assessed various circles not in accordance with agreed provisions, the disharmony and the inability of the manager in processing waste, and has not run the Intermediate Treatment Facility (ITF) waste management system. Waste management needs to build environmentally friendly waste technology because its legal umbrella already exists, such as Governor Regulation Number 50/2016 on the Construction and Operation of Municipal Waste Management Facility in the City.